Film jako medium edukacyjne - Jakubowski , Witold (Studia Edukacyjne, 2018)
Traditional thinking about applying films in educational activities was based on treating them as “didactic vehicles”. Thanks to that approach, it was possible to “smuggle” desirable values, create attitudes or to model pro-social behavior among students. That approach of using art as an education tool (not only films but other forms of art, too) should be understood and associated with the dominance of a communication model in education that is seen through the prism of three basic elements: sender – medium – recipient. Such a view neglects the recipient’s activity in constructing the sense of the work, assuming that the recipient has to “read and acquire” what the sender has offered him. The article, by referring not only to theoretical pedagogical positions, but also to media studies, film studies and cultural studies, considers the possibility of pedagogical application of film from the hermeneutic perspective.